A história do instituto universal brasileiro e a gênese da educação a distância no Brasil - Faria, Adriano Antonio (2010)
Distance education as a way of teaching that enables self-learning with the use of educational resources has been the subject of studies on its trajectory in the history of education. In this line of research work to understand the history of Brazilian education, and his subject of study is distance education as the object of research the Instituto Universal Brasileiro. The proposal raised questions about the trajectory of the IUB for the development of distance learning, reasons for its establishment, characterization of education as distance education or instruction, operation of courses, pedagogy and methodology adopted, the student's profile and disclosure of courses nationwide. Our main objective rescue the history of distance education in Brazil, with the benchmark creation and history of IUB in 1941. Specifically the intent is to expose the concepts and the historical evolution of distance education and to investigate the trajectory of IUB over his role in distance education, presents aspects of educational policy and understand the distance education in integrative dimension to the human . The methodological procedures include exploratory qualitative research design and historical research, conducted through documentary analysis. Results indicate the emergence of the IUB in a time when the national scene it configured by the dictatorial government of Getúlio Vargas, the Brazilian Industrial Revolution and suffered the consequences of World War II. The creation of the IUB came to meet the needs in the market regarding the growth of industrialization and lack of skilled technical professionals. The distance education began in 1941 with the first technical courses, distance education has to offer Supplemental courses of primary and secondary education at a distance for people over age 15 in 1995. The study confirms the IUB as a major distance education institutions in the country.